Semantics and Style - Ćarkić, Milosav Ž. (Stylistyka, 2008)
In this paper the author is trying to define the notions of semantics and style more accurately, and to establish a connection between them even though at first glance they are incompatible. Semantics as the study of meaning in linguistic terms according to empirical research into the structure and function of signs in natural languages reveals relations between them and the concepts they designate. Thus, in the context of structure, it explores lexical meaning, grammatical meaning, sentential meaning, and with respect to function descriptive meaning and associative meaning. Associative meaning covers several related types of meaning, dominated by the following three: stylistic, expressive and connota- tive. On this semantic plane style and semantics intersect, and partially overlap. Thus style, as the main generator of these three types of meaning, is directly correlated with semantics. Style and semantics are in a causal relationship: style is the cause (the generator of meaning), semantics the effect (the interpreter of meaning).